Lúpus eritematoso sistêmico juvenil: características clínico- epidemiológicas e fatores de risco à nefrite lúpica. - ALCÂNTARA, Carolina Tavares de (2022)
Juvenile Systemic Lupus Erythematosus (JSLE) is an inflammatory disease onset generalized chronic, autoimmune and multifactorial, culminating with the production of autoantibodies to nuclear antigens, resulting in a range of clinical manifestations, often of a more serious when there is involvement of the central nervous system and kidney, the latter called Lupus Nephritis (LN). This study soughtto identifytheclinical and epidemiological profileof patients with JSLEandanalyzethe factors associated withLNforcasesunder 16 years at Santa Casa de Misericordia do Para (FSCMPA), from January 2006 to January 2011. For this, we carried out a retrospective, descriptive and analytical, with a review of 20 charts of patients hospitalized with JSLE and / or attended the outpatient clinics of Nephrology and Rheumatology Children's FSCMPA, 17 of which were LN. TheFisher exact testand chisquare contingencywere usedtodeterminethe variablesassociated withtheNL, withsignificantvalues ofp≤0.05. The most common age range was 9 to 12 years (75%) and females were most affected (95%). The clinical manifestations most prevalent were: arthralgia (85%), followed by skin rash and photosensitivity malar (60%). The laboratory change was detected over the normochromic normocytic anemia (65%) and positivity of ANA was observed in all patients. The oral steroids were used as the main treatment, being employed in all patients, whereas in half of them were required pulse. The SLEDAI score showed higher severity in 75% of patients when applied to a first evaluation, from mild to moderate category for the last evaluation in 95% of cases. Sixtysix percent of patients had renal involvement at diagnosis. Edema (70.6%) and alteration of urinalysis (64.7%) were the most frequent renal manifestations, although the renal histological injury was the most prevalent type IV of the World Health Organization (WHO) changed. The largest number of diagnostic criteria (> 4) had a positive association (P ≤ 0.05) with the LN being appointed as the only risk factor. Among the many obstacles to the investigation of these patients is the small number of cases in a single center and the lack of a national and international consensus about its characteristics and clinical treatment, necessitating the need for further studies.